2014
DOI: 10.1016/j.bbapap.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Fc based antibody domains and fragments as novel scaffolds

Abstract: Therapeutic monoclonal antibodies (mAbs) have been successful for therapy of a number of diseases mostly cancer and immune disorders. However, the vast majority of mAbs approved for clinical use are full size, typically in IgG1 format. These mAbs may exhibit relatively poor tissue penetration and restricted epitope access due to their large size. A promising solution to this fundamental limitation is the engineering of smaller scaffolds based on the IgG1 Fc region. These scaffolds can be used for generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Indeed, a number of anti-FcgRI immunotoxins, composed of anti-FcgRI antibodies attached to various toxins, have recently been developed, and their efficacy has been demonstrated in vitro and in mouse models of different diseases, such as chronic cutaneous inflammation, rheumatoid arthritis, acute myeloid leukemia. 11,12,25,26,36,37 In this regard, the use of mFc to deliver therapeutic molecules could be particularly valuable because it provides extended circulating half-life and improved biodistribution by interacting with FcRn, 38,39 and it offers additional targeting to FcgRI-overexpressed cells, which in certain cases could lead to greater therapeutic benefit. For instance, one immediate application is to fuse mFc with anti-FcgRI immunotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of anti-FcgRI immunotoxins, composed of anti-FcgRI antibodies attached to various toxins, have recently been developed, and their efficacy has been demonstrated in vitro and in mouse models of different diseases, such as chronic cutaneous inflammation, rheumatoid arthritis, acute myeloid leukemia. 11,12,25,26,36,37 In this regard, the use of mFc to deliver therapeutic molecules could be particularly valuable because it provides extended circulating half-life and improved biodistribution by interacting with FcRn, 38,39 and it offers additional targeting to FcgRI-overexpressed cells, which in certain cases could lead to greater therapeutic benefit. For instance, one immediate application is to fuse mFc with anti-FcgRI immunotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with Heidelberg Pharma, they are exploring the use of this format for smaller ADCs using standard lysine chemistry in a HER2 model [106]. Fc-based binding fragments based on other technologies are emerging [107].…”
Section: Retaining the Fc Alonementioning
confidence: 99%
“…We devised a novel strategy to engineer FcRn binding into small-size antibody domains to explore whether their enhanced FcRn binding would correlate with prolonged in vivo half-life. [30][31][32] Our strategy used a combination of in silico and screening-based rational design to overcome the 2 limitations described above. Using molecular dynamics simulations, we found that CH2-CH3 hybrid structures with 8-mer peptide linkers between m01s and the CH3 FcRn-binding motif superimposed with the structure of Fc, and that a proline residue following the linker improved the backbone rigidity of the CH3 motif.…”
Section: Discussionmentioning
confidence: 99%